The value of air quality in Chinese cities: Evidence from labor and property market outcomes - Xuan Huang; Bruno Lanz (University of Neuchâtel, Institute of Economic Research (IRENE), 2017)
Using a dual-market sorting model of workers' location decisions, this paper studies the capitalization of air pollution in wages and property prices across Chinese cities. To account for endogeneity of air pollution in the determination of wages and property prices, we exploit quasi-experimental variations in air quality induced by a policy subsidizing coal-based winter heating in northern China, and document a discontinuity in average air quality for cities located north and south of the policy boundary. Using data for all 288 Chinese cities in 2011, we estimate an equilibrium relationship between wages and house prices for the entire system of Chinese cities, and specify a regression discontinuity design to quantify how variation in air quality induced by the policy affects this relationship locally. Our preferred estimates of the elasticity of wages and house prices with respect to PM10 concentration are 0.53 and -0.71 respectively. At the average of our sample, the willingness to pay for a marginal reduction in PM10 concentration is CNY 261.28 (about USD 40.50), with a significant share reflected in labor market outcomes.
Keywords: H41; J31; R31; Q53; 330; Hedonic model; Air pollution; Labor market; House prices; Local public goods; Regression discontinuity